STUDI PERILAKU HARIAN RUSA SAMBAR (Cervus unicolor) DI PENANGKARAN RUSA SAMBAR EDUPARK, BANJARBARU - Nadya Shafira Murpratiwi; Anni Nurliani (Universitas Lambung Mangkurat, 2023)
Sambar deer (Cervus unicolor) is one of the protected animals due to its small distribution in Indonesia. Sambar deer is distributed only in Sumatra and Kalimantan islands. South Kalimantan is one of the areas doing ex-situ conservation for this animal, such as sambar deer breeding in Edupark Banjarbaru. The knowledge related to behavior, food, water, shade, and space is important to fulfill the needs of animals in developing ex-situ conservation. The study aimed to determine the daily behavior of the sambar deer, which can be scientific information for reference in the conservation effort of sambar deer, especially in ex-situ conservation activities. Observations were made directly in the field using focal animal sampling and ad libitum methods. The focal animal sampling method is used to record the daily behavior of one individual (focal individual) at the same time. The ad libitum method is to record all observed behaviors of sambar deer. The results showed that sambar deer need shady places for rest and also places to wallow to minimize their body heat.